2001
DOI: 10.1292/jvms.63.1063
|View full text |Cite
|
Sign up to set email alerts
|

Tick-Encoded Serine Proteinase Inhibitors (Serpins); Potential Target Antigens for Tick Vaccine Development.

Abstract: ABSTRACT. Immunological protection of hosts against tick infestation is at present the most practically sustainable alternative tick control method to the current use of acaricides that is riddled with serious limitations. The current focus of tick vaccine research is the identification, cloning and in vitro production of recombinant tick vaccine candidate antigens. We have examined a selected number of reports on the roles of parasite-encoded members of the serine proteinase inhibitor (serpin) superfamily in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 62 publications
(63 reference statements)
1
52
0
Order By: Relevance
“…However, other authors have suggested that inhibitors such as serpin can be used by ticks to regulate endopeptidase activity and hemostasis (MULENGA et al, 2001(MULENGA et al, , 2003PERNER et al, 2016;TIRLONI et al, 2014). Peptidase inhibitors have been mentioned as effective antigens for preparing vaccines, because these genes are essential for the survival of ticks, since they are associated with endogenous processes such as regulation of hemolymph coagulation through controlling proteinase activity (IMAMURA et al, 2005).…”
Section: Blood Meal Digestion and Nutrient Uptakementioning
confidence: 99%
“…However, other authors have suggested that inhibitors such as serpin can be used by ticks to regulate endopeptidase activity and hemostasis (MULENGA et al, 2001(MULENGA et al, , 2003PERNER et al, 2016;TIRLONI et al, 2014). Peptidase inhibitors have been mentioned as effective antigens for preparing vaccines, because these genes are essential for the survival of ticks, since they are associated with endogenous processes such as regulation of hemolymph coagulation through controlling proteinase activity (IMAMURA et al, 2005).…”
Section: Blood Meal Digestion and Nutrient Uptakementioning
confidence: 99%
“…Given the importance of serpins in the regulation of mammalian host's physiological processes, it was hypothesized that ticks might encode serpins to evade host defense, and that blocking their function via immunization would compromise the tick's ability to feed (Mulenga et al, 2001;Mulenga et al, 2003). Indeed, a limited number of studies have reported mortality and reduced feeding efficiency in Ixodes ricinus Say (Prevot et al, 2007), Haemaphysalis longicornis Neuman (Sugino et al, 2003;Imamura et al, 2005) and Rhipicephalus appendiculatus Neuman (Imamura et al, 2005) ticks that fed on recombinant-serpin-immunized hosts.…”
Section: Introductionmentioning
confidence: 99%
“…In hypothesizing that tick-encoded serpins play key role(s) in regulating the evasion of host defense reactions by ticks (Prevot et al, 2007;Mulenga et al, 2001a;Mulenga et al, 2003;Mulenga et al, 2008, Mulenga et al, 2009, the underlying assumption is that ticks inject serpins into the host during tick feeding. In previous studies the basis for this assumption has been the expression of K. C. Chalaire and others Mr (kDa) RP 1 putatively extracellular serpin mRNA in tick salivary glands (Prevot et al, 2007;Prevot et al, 2006;Mulenga et al, 2003;Mulenga et al, 2008;Mulenga et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To complete feeding, ticks secrete enzymes that block inflammation and blood clotting, thus ensuring continued blood flow to the feeding site (Nuttall et al, 2006). Given that the host's primary lines of defense to tick feeding activity, inflammation and blood coagulation, are serine protease-mediated pathways that are regulated by serpins (Huntington, 2006;Gettins, 2002), it has been hypothesized that ticks may use serpins to evade the host's immune response (Mulenga et al, 2001a). An increasing number of serpin-encoding cDNAs have been identified in several tick species of medical and veterinary importance, including A. americanum (Mulenga et al, 2007), Haemaphysalis longicornis (Mulenga et al, 2001b;Imamura et al, 2005;Sugino et al, 2003), Ixodes ricinus (Prevot et al, 2006), I. scapularis (Mulenga et al, 2009) and Rhiphicephalus appendiculatus Imamura et al, 2006;Imamura et al, 2008).…”
Section: Introductionmentioning
confidence: 99%